Tinjauan Hukum Islam terhadap Jual Beli Barang Sitaan di Pondok Pesantren Al-Khoilily Ma’unah Sari Sampung Ponorogo - Siti Aminah Agustin; Ahmad Syafi'i SJ; Wahyudi Wahyudi (Social Science Academic, 2023)
Regulations and sanctions are two things that cannot be separated from Islamic boarding schools. One of the sanctions applied at the Al-Kholily Ma'unah Sari Islamic boarding school is the confiscation of students' items that are not placed in their proper place, in which the confiscated items will then be sold by the management. According to Syafi'iyah's fiqh study, it is required that goods that can be traded must be one's own property. While the practice of buying and selling confiscated goods carried out by management is still questionable about their ownership rights, whether the goods still belong to the santri or have become the property of the Islamic boarding school. The purpose of this study was to find out the review of Islamic law on the ownership status of confiscated goods at the Al-Kholily Ma'unah Sari Islamic Boarding School as well as to find out the review of Islamic law on the contract of sale and purchase of confiscated goods at the Al-Kholily Ma'unah Sari Islamic Boarding School. This type of research is field research using a qualitative descriptive approach. data collection obtained from observation, interviews and documentation. the results of this study show that the ownership rights of the goods traded by the management of the Al-Kholily Ma'unah Sari Islamic Boarding School belong to the boarding school. This can be seen because there was an agreement made by the management with the students so that the agreement indicated the willingness of the students if one day the goods were confiscated by the management and then sold. In this way the ownership rights of the confiscated goods are also automatically transferred to become the property of the cottage. Because the ownership status of the goods already belongs to the Islamic boarding school, the sale and purchase contract for confiscated goods at the Al-Kholily Ma'unah Sari Islamic Boarding School is legal. Because seen from the pillars and conditions have been fulfilled. In addition, this policy is also in line with the rule which states that the policy of a leader, in this case the management of the Al-Kholily Ma'unah Sari Islamic Boarding School for students, must be able to bring benefits. Keywords buying and selling; confiscated goods